2000
DOI: 10.1139/f00-045
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation and differential partitioning of polychlorinated biphenyls in freshwater, planktonic food webs

Abstract: Abstract:The planktonic food chain phytoplankton -zooplankton -young-of-the-year roach (Rutilus rutilus) was studied in 19 lakes in southern Sweden to investigate the bioaccumulation of polychlorinated biphenyls (PCBs). The SPCB concentrations did not steadily increase with increasing trophic level. The SPCB concentrations in zooplankton (400 ng·g lipid -1 ) were lower than in both phytoplankton (660 ng·g lipid -1 ) and fish (890 ng·g lipid -1 ), which did not differ significantly. Lipid content explained 40% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 41 publications
3
19
0
Order By: Relevance
“…These values are within 15 nPa of those predicted by the model of Fraser et al [22]. This suggests that the lipid fraction largely accounts for the measured bioaccumulation, consistent with the findings of Berglund et al [34]. 4) now follows the lipid fraction curve shown in Figure 2b.…”
Section: Application To Pcbs In Lake Ontariosupporting
confidence: 89%
See 1 more Smart Citation
“…These values are within 15 nPa of those predicted by the model of Fraser et al [22]. This suggests that the lipid fraction largely accounts for the measured bioaccumulation, consistent with the findings of Berglund et al [34]. 4) now follows the lipid fraction curve shown in Figure 2b.…”
Section: Application To Pcbs In Lake Ontariosupporting
confidence: 89%
“…Adare and Lasenby [33] suggest that the gender of a mysid also plays a role in the lipid content with mature mysids having a lipid content of 15 to 33% for females and 14 to 25% for males [33]. Berglund et al [34] suggested that lipid content explains 40% of the total variation in dry weight-normalized total PCB concentrations in samples from planktonic food chains, and Harding [35] suggested more generally that increases in lipid content in mysids and other zooplankton because of seasonal and size variations in the organism may increase organic contaminant concentrations. Berglund et al [34] suggested that lipid content explains 40% of the total variation in dry weight-normalized total PCB concentrations in samples from planktonic food chains, and Harding [35] suggested more generally that increases in lipid content in mysids and other zooplankton because of seasonal and size variations in the organism may increase organic contaminant concentrations.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Therefore, increased prey availability may permit zooplankton in eutrophic lakes to obtain the same amount of dietary lipids despite lower food quality of the individual phytoplankton. Also, it seems that there is no food chain biomagnification of PCBs in these planktonic food chains (Berglund et al 2000), so possible differences in phytoplankton PCB concentrations due to different trophic status may not be reflected in herbivores or consumers higher up in the food chain (Fig. This could have implications on the PCB accumulation in zooplankton.…”
Section: Discussionmentioning
confidence: 99%
“…However, those authors demonstrated a drastic decrease of the slope above a log K OW of six in the log‐log plot between the lipid‐normalized partition coefficient and K OW , and they interpreted this as biodilution in the zooplankton. Linear log K –log K OW relationships in zooplankton also have been reported, however, displaying slopes deviating from one [11]. Other investigators, based on PCB concentrations in zooplankton and prey, concluded that biomagnification did not have a significant effect on PCB concentrations in zooplankton.…”
Section: Introductionmentioning
confidence: 99%